FRI0513 Long-term (156 weeks) improvements in physical function of dmard-naÏve and dmard/biologic-experienced psoriatic arthritis patients treated with apremilast: data from a large database of 4 phase iii clinical trials. (15th June 2017) - Mease, PJ; Wells, A; Wollenhaupt, J; Hall, S; Bosch, F Van den; Lespessailles, E; McIlraith, M; Nguyen, D; Teng, L; Edwards, CJ
Abstract : Background: Improving and preserving patient (pt) physical function is an important goal for psoriatic arthritis (PsA). Objectives: To evaluate apremilast's (APR) effects on physical function/functional status for up to 3 yrs in DMARD/biologic-experienced (PALACE 1–3 [PAL1–3] pooled data) and DMARD-naive (PALACE 4 [PAL4]) pts with active PsA. Methods: Pts were randomized (1:1:1) to placebo (PBO), APR 30 mg BID (APR30), or 20 mg BID (APR20) at baseline (BL). The primary endpoint was at Wk16; a long-term extension is ongoing. A detailed study design has been previously presented. Assessed were mean change from BL HAQ-DI scores and proportions of pts reaching HAQ-DI MCID and reaching scores ≤1.0 (below clinically significant disability), ≤0.5 (minimal disability), and ≤0.25 (general population). Wk16 data were analyzed by LOCF. Wk156 data are as observed. Mean change and MCID outcomes are for all pts receiving APR30 at any time during the study; disability level data are for pts randomized to APR30 at BL. Results: PAL1–3 (biologic/DMARD-experienced) and PAL4 (DMARD-naïve) pts had similar BL SJC/TJC and DAS-28 (CRP), indicating active PsA. PAL1–3 pts had longer mean duration of PsA and psoriasis, higher PASI scores, and greater corticosteroid use at BL. Despite differences, BL physical disability was clinically significant in both populations (mean HAQ-DI, PAL1–3: 1.2; PAL4: 1.1). Marked disability at BL was seen in some pts randomized to APR30, with HAQ-DI scores up to 2.63–2.88. More PAL1–3 vs PAL4 APR30 pts had BL HAQ-DI >1.0 (60% vs 54%), >1.5 (marked difficulty/need for assistive devices, 31%vs 21%), and >1.75 (major disability, 19% vs 10%), highlighting need for early, effective treatment (tx). Few APR30 pts had BL scores ≤0.5 (18–22%) or ≤0.25 (10–14%). At Wk16, physical function significantly improved with APR30 vs PBO (mean HAQ-DI change, PAL1–3: −0.23 vs −0.08; PAL4: −0.21 vs 0.03; both P <0.0001) and more APR30 vs PBO pts reached HAQ-DI MCID ≥0.30 and ≥0.35. As early as Wk16, overall disability levels also shifted; more APR30 vs PBO pts achieved HAQ-DI ≤1.0 (PAL1–3: 56% vs 48%; PAL4: 60% vs 52%). At Wk156, marked achievement of HAQ-DI ≤1.0, ≤0.5, and ≤0.25 was observed in both populations (Table). LOCF analyses confirmed Wk156 results. Conclusions: With APR30 tx, physical disability improved early; functionality was maintained for up to 3 yrs. Most pts achieved HAQ-DI ≤1.0; many attained minimal/mild physical impairment. Over 40% of pts receiving APR30 earlier in the tx paradigm had functional ability similar to population norms after 3 yrs; shorter disease duration and no prior DMARD/biologics use in this population suggests that earlier APR tx may increase the likelihood of maximal functionality for some pts. Disclosure of Interest: P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, A. Wells Grant/research support from: Celgene Corporation, J. Wollenhaupt Grant/research support from: Abbott, BMS, MSD, Pfizer, UCB, Consultant for: Abbott, BMS, MSD, Pfizer, UCB, S. Hall Consultant for: Boehringer Ingelheim, MSD, Roche, Schering-Plough, Servier, Wyeth, Paid instructor for: Amgen, AstraZeneca, Boehringer Ingelheim, Centocor, GSK, MSD, Pfizer, Sanofi Aventis, Sanofi Pasteur, Schering-Plough, Serono, Wyeth, Speakers bureau: Boehringer Ingelheim, GSK, MSD, Pfizer, Roche, Sanofi Aventis, Schering-Plough, Wyeth, F. Van den Bosch Consultant for: AbbVie, Celgene Corporation, Merck, Pfizer, UCB, Janssen, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, Servier, M. McIlraith Employee of: Celgene Corporation, D. Nguyen Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, C. Edwards Grant/research support from: Celgene Corporation, Pfizer, Roche, Samsung, Consultant for: Celgene Corporation, Pfizer, Roche, Samsung, Speakers bureau: Abbott, GSK, Pfizer, Roche